Impact of copper-titanium carbide tooltip on machined surface integrity during electrical discharge machining of EN31 steel. (28th August 2019) - Walia, Arminder Singh; Srivastava, Vineet; Jain, Vivek
Abstract: In electrical discharge machining, wear of tool electrode is a significant problem. The effect of wear is also transferred to the workpiece reflecting as surface roughness and also affects surface integrity. Therefore, this work investigates the effect of process parameters namely discharge current, gap voltage, pulse on time, pulse off time and dielectric flushing pressure on surface morphology and topography of EN31 die steel during electrical discharge machining using copper-titanium carbide tooltip. Evidence points to melting and evaporation as the most significant material removal mechanism. The surface roughness was measured for the workpieces machined by cermet and copper tooltips and the surface roughness was higher in the workpieces machined by cermet tooltip. However, when percentage rise of surface roughness of workpiece was compared, it was found that cermet tooltip contributed lesser to the increase in surface roughness. A model for predicting surface roughness has been developed. ANOVA was used to establish the adequacy of the model. It was found that discharge current, pulse on time, pulse off time and flushing pressure are the major variables influencing surface roughness of the workpiece. Increasing discharge current, pulse on time and pulse off time causes increment in surface roughness. Surface roughness reduces with amplification in flushing pressure. Confirmation experiments established that predicted values of the model was in agreement with experimental observations. The morphology and topography of the machined surface has been studied using scanning electron microscopy. The surface irregularities increases with increase in discharge current, pulse on time, pulse off time and decreased with increase in flushing pressure. Lesser surface irregularities, cracks and voids were observed on workpiece machined by cermet tooltip. The hardness value of the machined surface was found to be higher for workpieces machined by cermet tooltip as compared to workpieces machined by copper tooltip.